Two new and one known species of Phanodermatidae (Nematoda: Enoplida) from Sagami Bay, Japan - Shimada, Daisuke; Kakui, Keiichi (Zootaxa, 2019)
Two new and one known species of free-living marine nematode belonging to the family Phanodermatidae are described. They were collected during the 12th Japanese Association for Marine Biology (JAMBIO) Coastal Organism Joint Survey off Jogashima, Japan in Sagami Bay, North Pacific Ocean. Phanodermopsis kohtsukai sp. nov. differs from the congeners by the shape of the tail, the longer spicules, and the absence of the gubernaculum. Micoletzkyia nakanoi sp. nov. differs from the congeners by the absence of a circle of cervical setae, the proportion of the tail, the cylindrical gubernaculum without projection, and the position of the vulva. Crenopharynx caudata (Filipjev, 1927) comb. nov. is transferred from the genus Phanodermopsis based on the presence of the long spicules. The morphological characters of the newly collected specimens of C. caudata comb. nov. are in excellent agreement with those shown in the original description of the specimens from Arctic Russia and the previous redescription of the specimens from Skagerrak. The new diagnoses and species lists for these three genera and two dichotomous keys to the males of Micoletzkyia and Crenopharynx are provided.